2018
DOI: 10.1159/000490686
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Chronic Kidney Disease Affects HDL Impact on Lipoprotein Lipase (LPL)-Mediated VLDL Lipolysis Efficiency

Abstract: Background/Aims: Hypertriglyceridaemia (HTG) and reduction and dysfunction of high density lipoprotein (HDL) are common lipid disturbances in chronic kidney disease (CKD). HTG in CKD is caused mainly by the decreased efficiency of lipoprotein lipase (LPL)-mediated very low density lipoprotein triglyceride (VLDL-TG) lipolysis. It has not been clarified whether HDL dysfunction in CKD contributes directly to HTG development; thus, the aim of this study was to assess the impact of CKD progression on the ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 30 publications
3
27
0
2
Order By: Relevance
“…Oxidative modifications of HDL are thought to contribute to the formation of dysfunctional proinflammatory HDL. Moreover,Ćwiklińska et al [69] demonstrated that in CKD patients the positive effect of HDL on the efficiency of VLDL lipolysis was modified. They found that the efficacy of VLDL lipolysis in the presence of HDL was, in non-CKD patients, significantly higher than in those with CKD and it decreased with a reduction in estimated glomerular filtration rate (eGFR).…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…Oxidative modifications of HDL are thought to contribute to the formation of dysfunctional proinflammatory HDL. Moreover,Ćwiklińska et al [69] demonstrated that in CKD patients the positive effect of HDL on the efficiency of VLDL lipolysis was modified. They found that the efficacy of VLDL lipolysis in the presence of HDL was, in non-CKD patients, significantly higher than in those with CKD and it decreased with a reduction in estimated glomerular filtration rate (eGFR).…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…It seems that HDL disturbances in CKD play a key important role in retarded VLDL catabolism and the development of hypertriglyceridemia. The increased levels of pre-β HDL subpopulation, which acts as LPL inhibitor, may explain the impact of HDL disturbances on VLDL lipolysis efficiency [69,70]. Additionally, modifications of VLDL and HDL composition and properties influencing their interactions may affect lipolysis; negative correlations were revealed between lipolysis efficiency and apoE and apoCs content in VLDL as well as a positive relationship between lipolysis and HDL-apoC-II and VLDL and HDL apoC-II/apoC-III ratios [69].…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…La pacienţii HiV pozitiv, homozigozitatea apo ε4 ne arată progresia spre SiDa şi creşterea susceptibilitităţii la infecţii oportuniste. apoe plasmatică apare în principal prin sinteză hepatică; la nivel cerebral, astrocitele produc o cantitate mare de lichid cefalorahidian ce conţine apoe (23,24,25). aSoCIEREa apoE cu unElE afEcţiuni apo ε4 aste asociată cu boala alzheimer familială cu debut tardiv.…”
Section: Caracteristicile Genotipurilor Apoe (Alele ε2 ε3 ε4)unclassified